2020
DOI: 10.1029/2019jd030923
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Stratosphere in Subseasonal to Seasonal Prediction: 2. Predictability Arising From Stratosphere‐Troposphere Coupling

Abstract: The stratosphere can have a significant impact on winter surface weather on subseasonal to seasonal (S2S) timescales. This study evaluates the ability of current operational S2S prediction systems to capture two important links between the stratosphere and troposphere: (1) changes in probabilistic prediction skill in the extratropical stratosphere by precursors in the tropics and the extratropical troposphere and (2) changes in surface predictability in the extratropics after stratospheric weak and strong vort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
175
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

5
5

Authors

Journals

citations
Cited by 180 publications
(185 citation statements)
references
References 132 publications
10
175
0
Order By: Relevance
“…Europe (from a lag of 20 days onwards) and later shifting towards Scandinavia. This is in stark contrast to the negative NAO and the associated cold conditions that are commonly expected as the canonical response to SSWs over Europe (Butler et al, 2017;Kolstad et al, 2010;Domeisen et al, 2019a).…”
Section: Consistent Withmentioning
confidence: 82%
“…Europe (from a lag of 20 days onwards) and later shifting towards Scandinavia. This is in stark contrast to the negative NAO and the associated cold conditions that are commonly expected as the canonical response to SSWs over Europe (Butler et al, 2017;Kolstad et al, 2010;Domeisen et al, 2019a).…”
Section: Consistent Withmentioning
confidence: 82%
“…5a. However, the WCR is not a common precursor of SSWs (Domeisen et al 2020), and Karpechko (2018) found that this SSW was only predictable up to 10 days in advance in the ECMWF model. There was also no obvious subsequent impact of the SSW on our North American weather regimes in February-March 2009.…”
Section: Subseasonal Forecast Evolutionmentioning
confidence: 95%
“…Hence, there are several opportunities yet to explore in further work related to atmospheric probing and data assimilation using infrasound datasets. A long-term objective is to enhance or constrain the representation of stratospheric winds in global models, thereby contributing to enhanced surface weather predictions on subseasonal-to-seasonal time-scales (Domeisen et al, 2020a;2020b).…”
Section: Summary and Future Workmentioning
confidence: 99%